Biocontrol of Listeria monocytogenes in a meat model using a combination of a bacteriocinogenic strain with curing additives - Orihuel, Alejandra (2018)
The aim of this work was to evaluate the effect of meat curing agents on the bioprotective activity of the bacteriocinogenic strain, Enterococcus (E.) mundtii CRL35 against Listeria (L.) monocytogenes during meat fermentation. The ability of E. mundtii CRL35 to grow, acidify and produce bacteriocin in situ was assayed in a meat model system in the presence of curing additives (CA). E. mundtii CRL35 showed optimal growth and acidification rates in the presence of CA. More importantly, the highest bacteriocin titer was achieved in the presence of these food agents. In addition, the CA produced a statistical significant enhancement of the enterocin CRL35 activity. This positive effect was demonstrated in vitro in a meat based culture medium, by time-kill kinetics and finally by using a beaker sausage model with a challenge experiment with the pathogenic L. monocytogenes FBUNT strain. E. mundtii CRL35 was found to be a promising strain of use as a safety adjunct culture in meat industry and a novel functional supplement for sausage fermentation, ensuring hygiene and quality of the final product.